2006
DOI: 10.1109/mtv.2006.20
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Static Timing Analysis Considering the Impact of Power Supply Noise in VLSI Circuits

Abstract: Chair of Advisory Committee: Dr. Duncan Moore Henry Walker As semiconductor technology is scaled and voltage level is reduced, the impact of the variation in power supply has become very significant in predicting the realistic worst-case delays in integrated circuits. The analysis of power supply noise is inevitable because high correlations exist between supply voltage and delay. Supply noise analysis has often used a vector-based timing analysis approach. Finding a set of test vectors in vector-based approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…As supply voltages are lowered, the sensitivity of path delay to power supply noise increases. It has been shown that a 10% decrease in the power/ground supply voltages increases path delay by about 8% in 180nm designs [1], 30% in 13 0nm technologies and a 1 % varia tion in power supply in 90nm leads to 4% increase in 276 delay respectively [2] [7]. This trend shows the growing need to study the effect of power supply noise on path delay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As supply voltages are lowered, the sensitivity of path delay to power supply noise increases. It has been shown that a 10% decrease in the power/ground supply voltages increases path delay by about 8% in 180nm designs [1], 30% in 13 0nm technologies and a 1 % varia tion in power supply in 90nm leads to 4% increase in 276 delay respectively [2] [7]. This trend shows the growing need to study the effect of power supply noise on path delay.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence probabilities of voltage drops is then calculated by performing power analysis which is then used to estimate the extra delay induced by the IR -drop. Another statistical vectorless approach is proposed in [2] where supply voltage noise analysis is incorporated into static timing analysis (STA). The authors have estimated the noise based on different circuit models proposed in [9] with and with out the consideration of don't care bits.…”
Section: Introductionmentioning
confidence: 99%
“…However, the circuit size they reported [10] was limited, and its application to larger circuits was not clarified. Statistical treatment has been introduced into power supply noise-aware timing analysis [11]- [13] as another approach. Pant et al [11] estimated the voltage variations by convoluting statistically modeled current consumption and the impulse response of a power/ground network.…”
mentioning
confidence: 99%
“…Jiang and Chen [12] first derived the average and standard deviation of all blocks and the correlation coefficients between the blocks, and they then estimated the delay. Kim and Walker [13] focused on the spatial correlation of power supply noise and proposed using principal component analysis (PCA) to model power supply noise. The path-delay distribution was then computed with uncorrelated variables.…”
mentioning
confidence: 99%
See 1 more Smart Citation